CRITICAL STUDY OF EDUCATIONAL THOUGHTS OF GANDHI AND RAJNEESH - Kumar Teotia, Dr. Anil; Rani , Pooja (Innovative Research Thoughts, 2017)
Mahatma Gandhi and Acharya Rajneesh had different areas of work. Both favoured the development of human sensibilities excellent human qualities and inherent powers that genuinely make humans. Both Gandhi and Rajneesh have not considered education as a means of earning a living. Both consider education as a means of developing unlimited possibilities for humans. According to Gandhi, knowledge should be useful for the welfare of humankind, and education should be free from all kinds of Slavery. Gandhi considered experience as a means of practicable. Rajneesh considers education to be essential for human development. According to him, the nature of the human race rests on education. He says "The basic Reason why humankind is trapped in its ugliness and disability is hidden in education itself. According to Gandhi, the main aim of education is character building. He considered the character to be the centre of education."He says that your education is meaningless. If it is not given on the concreate plane of truth and purity. According to Rajneesh, women should not imitate men. It is necessary to do some work in the direction that a woman is available in her nature, with full dignity. Being educated like a man, the woman becomes a fake man could not be a real woman. In this article, researchers tried to explore various thoughts of Gandhi and Rajneesh about education.